Analisis Pengaruh Biaya Promosi Terhadap Minat Calon Mahasiswa Untuk Studi Di Institut Bisnis Dan Informatika Stikom Surabaya - Yuliana, Eka; Sulistyowati, Sulistyowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Promotion to SMA/SMK/MA to interest and attract prospective students continue studying in Stikom Surabaya is the task of the sections Public Relation and Marketing (PRM). In conducting promotional activities needed for these promotional purposes so that the cost can be achieved. However, the total cost of the promotion has been issued every year increase, while the number of new student admissions data in Stikom Surabaya has decreased each year. The cost of the promotion is divided into seven groups of costs relevant to the interest of prospective new students. Therefore there is a need for research of the promotion costs which are the seventh most influential significantly to new student interest.This is done as a consideration of decision-making so that promotional costs can be optimized in the coming year. The evaluation is done by doing a cost analysis and new student interest. The analysis method using multiple linear regression.